Transfer of a Catabolic Pathway for Chloromethane in Methylobacterium Strains Highlights Different Limitations for Growth with Chloromethane or with Dichloromethane - Michener, Joshua K.; Vuilleumier, Stéphane; Bringel, Françoise; Marx, Christopher J. (Frontiers in Microbiology, 2016)
Chloromethane is an ozone-depleting gas, produced predominantly from natural sources, that provides an important carbon source for microbes capable of consuming it. Chloromethane catabolism has been difficult to study owing to the challenging genetics of its native microbial hosts. Since the pathways for chloromethane catabolism show evidence of horizontal gene transfer, we reproduced this transfer process in the laboratory to generate new chloromethane-catabolizing strains in tractable hosts. We demonstrate that six putative accessory genes improve chloromethane catabolism, though heterologous expression of only one of the six is strictly necessary for growth on chloromethane. In contrast to growth of Methylobacterium strains with the closely-related compound dichloromethane, we find that chloride export does not limit growth on chloromethane and, in general, that the ability of a strain to grow on dichloromethane is uncorrelated with its ability to grow on chloromethane. This heterologous expression system allows us to investigate the components required for effective chloromethane catabolism and the factors that limit effective catabolism after horizontal transfer.